Acrylic‐Acid‐Functionalized PolyHIPE Scaffolds for Use in 3D Cell Culture. Issue 23 (14th November 2013) - Hayward, Adam S.; Sano, Naoko; Przyborski, Stefan A.; Cameron, Neil R.
<x xml:space="preserve">Abstract</x> This study describes the development of a functional porous polymer for use as a scaffold to support 3D hepatocyte culture. A high internal phase emulsion (HIPE) is prepared containing the monomers styrene (STY), divinylbenzene (DVB), and 2‐ethylhexyl acrylate (EHA) in the external oil phase and the monomer acrylic acid (Aa) in the internal aqueous phase. Upon thermal polymerization with azobisisobutyronitrile (AIBN), the resulting porous polymer (polyHIPE) is found to have an open‐cell morphology and a porosity of 89%, both suitable characteristics for 3D cell scaffold applications. X‐ray photoelectron spectroscopy reveals that the polyHIPE surface contained 7.5% carboxylic acid functionality, providing a useful substrate for subsequent surface modifications and bio‐conjugations. Initial bio‐compatibility assessments with human hepatocytes show that the acid functionality does not have any detrimental effect on cell adhesion. It is therefore believed that this material can be a useful precursor scaffold towards 3D substrates that offer tailored surface functionality for enhanced cell adhesion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>